Opening the borders: immigration policy, migrants' selection and human capital accumulation - Giorgio Bellettini; Carlotta Berti Ceroni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
This paper investigates the economic consequences of international migration from the point of view of destination countries. Consistently with international evidence on migration flows, we build a model where the migration rate is higher among the highlyeducated. A negative relationship is shown to exist between the domestic wage level and the percentage of educated workers among immigrants, which raises interesting policy implications. In particular, the optimal immigration policy from the point of view of natives requires an immigration quota above a certain minimum level. Extending the analysis to a dynamic setting, we highlight additional effects of the immigration quota on human capital accumulation among natives.
Keywords: 330